Front Cover: Synthesis of Tetra‐Substituted Trifluoromethyl‐3, 1‐Benzoxazines by Transition‐Metal‐Catalyzed Decarboxylative Cyclization of N‐Benzoyl Benzoxazinones (ChemistryOpen 5/2021). Issue 5 (4th May 2021) - Uno, Hiroto; Fujimoto, Daichi; Harada, Kyosuke; Tanaka, Chika; Shibata, Norio
Abstract : The Front Cover is inspired by the diversity in the ocean also in cyberspace. In the present research, we can synthesize diverse heterocyclic molecules having a trifluoromethyl group in a single step by changing the N ‐substitution. You can see more variations of trifluoromethyl heterocycles in several papers by our group. More information can be found in the Communication by Hiroto Uno et al .